A Case Study of Reliability and Performance of the Electric Power Distribution Station Based on Time between Failures. (10th October 2013) - Baharum, Adam; Alwan, Faris Mahdi; Hasson, Saad Talib
Abstract : This paper presents an algorithm for estimating the performance of high-power station systems connected in series, parallel, and mixed series-parallel with collective factor failures caused by any part of the system equipment. Failures that occur frequently can induce a selective effect, which means that the failures generated from different equipment parts can cause failures in various subsets of the system elements. The objectives of this study are to increase the lifetime of the station and reduce sudden station failures. The case study data was collected from an electricity distribution company in Baghdad, Iraq. Data analysis was performed using the most valid distribution of the Weibull distribution with scale parameter α = 1.3137 and shape parameter β = 94.618. Our analysis revealed that the reliability value decreased by 2.82% in 30 days. The highest critical value was obtained for components T1, CBF5, CBF7, CBF8, CBF9, and CBF10 and must be changed by a new item as soon as possible. We believe that the results of this research can be used for the maintenance of power systems models and preventive maintenance models for power systems.